The nature of confidentiality - Thompson, I. E. (Journal of medical ethics, 1979)
This paper examines confidentiality and its nature and analyses the guidelines laid down by the Hippocratic Oath as well as the British and World Medical Associations for maintaining such confidentiality between doctor and patient. There are exceptions to practically any code of rules and this is true also for confidentiality. Some of these exceptions make it appear that very little is confidential. The three values implicit in confidentiality would seem to be privacy, confidence and secrecy. Each of these values is discussed and developed in this paper. In conclusion, the question is suggested that maybe in the face of death, doctor and patient need to re-examine the pre-suppositions of privacy, confidence and secrecy on which the confidential relationship is based.